Microscopic characteristics, total phenolic content and antioxidant activity of Zingiber nudicarpum - Nguyen, Dinh Quynh Phu; Doan, Quoc Tuan; Huynh, Van Quynh (Tạp chí Y Dược Huế, 2024)
Background: Zingiber Mill. is one of the most diverse genera in Vietnam with 36 recorded species, many of which have been used as traditional medicine to treat several ailments. Reports of studies on Z. nudicarpum D. Fang are relatively scarce. Objectives: This study aimed to determine the microscopic characteristics, total phenolic content and antioxidant activity of Z. nudicarpum. Materials and methods: Z. nudicarpum was collected in Phong Dien district, Thua Thien Hue province. Anatomic features and powder characteristics were determined by the microscopic methods. The Folin-Ciocalteau method and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay were used to analysis the total phenolic content (TPC) and antioxidant potential, respectively. Results: The microscopic characteristics of the leaves and roots of Z. nudicarpum have been reported. The ethanol extract from the aerial part of Z. nudicarpum exhibited a notable amount of phenolic content and antioxidant activity than the underground part extract. The total phenolic content in the aerial and underground parts extract were 373.41 ± 1.50 mg GAE/g extract and 61.27 ± 1.65 mg GAE/g extract, respectively. The highest DPPH radical scavenging effect was observed in the aerial part with IC50 value of 4.86 ± 0.08 μg/mL, while it was not found in the extract from the underground part (IC50 > 500 μg/mL). Conclusion: This is the first report on the microscopic features, total phenolic content and antioxidant capacity of Z. nudicarpum.